Accessibility to dental care for patients with special needs - Cíntia Yuki Fukuoka; Edgard Michel-Crosato; Ismar Eduardo Martins Filho; Maria Gabriela Haye Biazevic; Wellington Menyrval Zaitter (Revista Sul-Brasileira de Odontologia, 2012)
Introduction and objective: The aim of this study was to verify the professionals’ perception about the accessibility to dental care establishments for three types of patients with special needs: Diabetes, AIDS, and Cerebral Paralysis patients, in the city of São Paulo. Material and methods: This was a descriptive, cross-sectional study with a non probabilistic sample. For the analysis, 107 dental care establishments were selected and divided into two categories (private and insurance). Each one of the establishments was randomly selected from a list containing a total of 3,234 private and 2,015 insurance establishments. The information for the study was based on phone conversations, when a semi-structured interview was accomplished to verify the accessibility for AIDS, Diabetes, and Cerebral Paralysis special need patients. The analysis of the interviews’ content was executed according to the methodology of Lefèvre and Lefèvre (2000) and in agreement with the central idea. Results: From the total of participants, 55.14% were female and 53.27% worked at a private clinic. In relation to the patients’ accessibility, 96.26% had already treated Diabetes patients, 55.14% AIDS patients, and 28.97% Cerebral Paralysis patients. Conclusion: It can be concluded that concerning to Diabetes patients, the main difficulty is the clinical practice, mainly related to problems in blood coagulation. For Cerebral Paralysis patients, the difficulties were related to personnel training, establishment structure, and also clinical practice. For AIDS patients, although difficulties in clinical practice were mentioned, prejudice still seemed to be the major difficulty.